Silencing I2PP2A Rescues Tau Pathologies and Memory Deficits through Rescuing PP2A and Inhibiting GSK-3β Signaling in Human Tau Transgenic Mice - Zhang, Yao; Ma, Rong-Hong; Li, Xia-Chun; Zhang, Jia-Yu; Shi, Hai-Rong; Wei, Wei; Luo, Dan-Ju; Wang, Qun; Wang, Jian-Zhi; Liu, Gong-Ping (Frontiers in Aging Neuroscience, 2014)
Increase of inhibitor-2 of protein phosphatase-2A (I2PP2A) is associated with PP2A inhibition and tau hyperphosphorylation in Alzheimer’s disease (AD). Down-regulating I2PP2A attenuated amyloidogenesis and improved the cognitive functions in transgenic mice expressing amyloid precursor protein (tg2576). Here, we found that silencing I2PP2A by hippocampal infusion of Lenti-siI2PP2A downregulated I2PP2A (~45%) with reduction of tau phosphorylation/accumulation, improvement of memory deficits and dendritic plasticity in 12-month old human tau transgenic mice. Silencing I2PP2A not only restored PP2A activity but also inhibited glycogen synthase kinase 3β (GSK-3β) with a significant activation of protein kinase A (PKA) and Akt. In HEK293/tau and N2a/tau cells, silencing I2PP2A by pSUPER-siI2PP2A also significantly reduced tau hyperphosphorylation with restoration of PP2A activity and inhibition of GSK-3β, demonstrated by the decreased GSK-3β total protein and mRNA levels, and the increased inhibitory phosphorylation of GSK-3β at serine-9. Furthermore, activation of PKA but not Akt mediated the inhibition of GSK-3β by I2PP2A silencing. We conclude that targeting I2PP2A can improve tau pathologies and memory deficits in htau transgenic mice, and activation of PKA contributes to GSK-3β inhibition induced by silencing I2PP2A in vitro, suggesting that I2PP2A is a promising multiple target of AD.